Phenotypic plasticity of eddoe and dasheen taro genotypes in response to saturated water and dryland cultivations (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hidayatullah CSR, Santosa E, Sopandie D, Hartono A. 2020. Phenotypic plasticity of eddoe and dasheen taro genotypes in response to saturated water and dryland cultivations. Biodiversitas 21: 4550-4557.  The phenotypic plasticity of dasheen and eddoe taro genotypes was evaluated based on growth and yield characters to select proper genotypes in response to climate change. The study was conducted at the Leuwikopo Experimental Farm, Bogor, Indonesia from May to October 2019. Dasheen (Talas Sutra and Talas Bentul) and eddoe genotypes (S28 and S19) were planted in saturated water cultivation (SWC) and dryland cultivation (DC). DC relied on rainwater, and SWC was manipulated dryland by flooding. SWC promoted vigorous growth and tuber weight, irrespective of genotypes. Increasing taro biomass production in SWC was supported by higher photosynthetic rate, leaf number, and size. Dasheen genotypes produced higher tuber weight than the eddoe in SWC, conversely, the eddoe tended to produced heavier tuber than the dasheen in DC; indicating phenotypic plasticity is strongly affected by soil moisture and genotype. The dasheen had more plastic growth and yield characters to soil moisture than the eddoe genotypes, with plasticity level, ranging from low to very high. Taro had high resiliency to multiple abiotic stresses, e.g. flood, and drought. Considering the marketable value of the yield, dasheen and eddoe genotypes are recommended in flooding and drought-prone areas, respectively.
Keywords: Climate change, Colocasia esculenta, drought, multiple abiotic stress, yield